(untitled) (Research, Society and Development, 2021)
Introduction: The thrombin generation assay (TGA) assesses the risk of developing thrombotic events. The aim of this study was to investigate the association between the use of oral contraceptives (OCs) and hormone therapy (HT) with the TGA and resistance to activated protein C (APC). Methods: Cross-sectional study with women from the Longitudinal Study of Adult Health (ELSA-Brasil). TGA was performed by the CAT method. Results: There was an association between all parameters of the TGA and the use of OCs and an association of lag time and peak time with the use of HT. Conclusion: The TGA allows us to assess the hypercoagulability status and may be useful in the management of female hormones users.